Monoamine oxidase a gene promoter methylation and transcriptional downregulation in an offender population with antisocial personality disorder. (March 2015) - Checknita, D.; Maussion, G.; Labonté, B.; Comai, S.; Tremblay, R. E.; Vitaro, F.; Turecki, N.; Bertazzo, A.; Gobbi, G.; Côté, G.; Turecki, G.
Abstract : Background: Antisocial personality disorder (ASPD) is characterised by elevated impulsive aggression and increased risk for criminal behaviour and incarceration. Deficient activity of the monoamine oxidase A ( MAOA ) gene is suggested to contribute to serotonergic system dysregulation strongly associated with impulsive aggression and antisocial criminality. Aims: To elucidate the role of epigenetic processes in altered MAOA expression and serotonin regulation in a population of incarcerated offenders with ASPD compared with a healthy non-incarcerated control population. Method: Participants were 86 incarcerated participants with ASPD and 73 healthy controls. MAOA promoter methylation was compared between case and control groups. We explored the functional impact of MAOA promoter methylation on gene expression in vitro and blood 5-HT levels in a subset of the case group. Results: Results suggest that MAOA promoter hypermethylation is associated with ASPD and may contribute to downregulation of MAOA gene expression, as indicated by functional assays in vitro, and regression analysis with whole-blood serotonin levels in offenders with ASPD. Conclusions: These results are consistent with prior literature suggesting MAOA and serotonergic dysregulation in antisocial populations. Our results offer the first evidence suggesting epigenetic mechanisms may contribute to MAOA dysregulation in antisocial offenders.